Aspectos alelopáticos, fitoquímicos e anatômicos do capim-annoni : (eragrostis plana nees) - Favaretto, Adriana (2015)
The tough lovegrass (Eragrostis plana Nees) is the main invasive of natural pastures of southern Brazil, whose expansion is partly attributed to its allelopathic potential. This study, unpublished for the plant, aimed to verify the autotoxicity, chemical composition and anatomical/histochemical characteristics of this grass, through three experiments: 1) The autotoxicity of aqueous extracts of leaves and roots at germination and seedling growth of the species was performed with extracts from green leaves, senescent leaves and roots at concentrations of 0.05, 0.15 and 0.25 g.mL-1. It was observed that the occurrence of autotoxicity, regardless of the source material and concentration; 2) The identification of the main chemical groups, potentially allelopathics, presents in leaves and roots, was performed by means of general tests, by thin layer chromatography (TLC) and by high performance liquid chromatography (HPLC), duly validated. General tests showed the presence of saponins, alkaloids and flavonoids in leaves and roots, and tannins in leaves only. By TLC, alkaloids and saponins were detected; by HPLC, was verified the presence of coumarin in the same amount in leaves and roots, ferulic acid, in greater amounts in the roots, caffeic acid, p-coumaric acid and vanillic acid in larger quantities in leaves, and catechin and epicatechin, only the leaves; 3) To anatomical and histochemical analysis, leaves and roots of plants in vegetative stage were collected. For anatomy, leaf blades and roots were collected, fixed in FAA 70, sectioned, stained and photographed in light microscope. For histochemical analysis, sections on newly collected leaves and roots were performed. The segments were subjected to specific reagents to determine lipids, phenols, tannins, lignin, alkaloids and starch. It was observed that the leaves have epidermis with lignified cells, Kranz structure, collateral vascular bundles of two sizes and needle-shaped trichomes. The roots have air gaps on the cortical parenchyma, forming the aerenchyma; the endoderm has U shaped thickening and pith parenchymatic has cells with starch storage plastids. Leaves and roots have lipids, phenolic compounds, lignin and alkaloids, but the starch was observed only at the root. The anatomical and histochemical characters of tough lovegrass may be associated with their high adaptation to compacted soils, as well as its tolerance to herbivory, abiotic and biotic stresses